Natural variation in a molybdate transporter controls grain molybdenum concentration in rice. Issue 4 (23rd November 2018) - Huang, Xin‐Yuan; Liu, Huan; Zhu, Yu‐Fei; Pinson, Shannon R. M.; Lin, Hong‐Xuan; Guerinot, Mary Lou; Zhao, Fang‐Jie; Salt, David E.
Summary: Molybdenum (Mo) is an essential micronutrient for most living organisms, including humans. Cereals such as rice ( Oryza sativa ) are the major dietary source of Mo. However, little is known about the genetic basis of the variation in Mo content in rice grain. We mapped a quantitative trait locus (QTL) qGMo8 that controls Mo accumulation in rice grain by using a recombinant inbred line population and a backcross introgression line population. We identified a molybdate transporter, OsMOT1;1, as the causal gene for this QTL. OsMOT1;1 exhibits transport activity for molybdate, but not sulfate, when heterogeneously expressed in yeast cells. OsMOT1;1 is mainly expressed in roots and is involved in the uptake and translocation of molybdate under molybdate‐limited condition. Knockdown of OsMOT1;1 results in less Mo being translocated to shoots, lower Mo concentration in grains and higher sensitivity to Mo deficiency. We reveal that the natural variation of Mo concentration in rice grains is attributed to the variable expression of OsMOT1;1 due to sequence variation in its promoter. Identification of natural allelic variation in OsMOT1;1 may facilitate the development of rice varieties with Mo‐enriched grain for dietary needs and improve Mo nutrition of rice on Mo‐deficient soils.